Academic libraries: service performance model at research university (RUs) in Malaysia / Aishah Musa ... [et al.] - Musa, Aishah; Ismail, Junaida; Harun, Etty Harniza; Shaari, Sharunizam; Ladisma@Awis, Mahadir (2019)
There are four (4) research universities in Malaysia namely, Universiti Sains Malaysia (USM), Universiti Putra Malaysia (UPM), Universiti Malaya (UM) and Universiti Kebangsaan Malaysia (UKM). As part of the entity of a Research University the academic library should play an utmost role to achieve the goals in providing and sharing the up-to-date knowledge to the community of the Research University. An academic library should play the greatest role and performs its task as the centre of knowledge and parallel its performance with the research university status. With that it can encourage the researchers in the world wide to come and get the services from the academic libraries at the RUs. The performance of an academic library can be measured based on several elements i.e. the number of books on the shelf, the treatment given by their staff, the library collection is up-to-date, accurate information that can be shared by their staff, accessibility to internet access, or access to an online database. Previous researches exposed that the performance and worth of an academic library in meeting the user's needs were conventionally measured using several instruments like the size of collection, budget, expenditure and staff (Nitecki & Franklin, 1999). According to Kasmarini Baharuddin (2015), the basic idea for the academic library is it should have an organised collection of books and other materials used to study, journal collections to help in doing a research and a recreation place in a building that houses such a collection. The main purpose of having a library is to provide information to its users (Rowley, 1996). Besides that, satisfying users' needs in academic libraries has been the primary objective of the libraries and librarians (Norliya, 2009).